Artificial Fusion Protein to Facilitate Calcium Carbonate Mineralization on Insoluble Polysaccharide for Efficient Biocementation - Nawarathna, T.H.K.; Kawabe, Tetsuya; Mwandira, Wilson; Kurumisawa, Kiyofumi; Kawasaki, Satoru (University of Jaffna, 2021)
Biomineralization is a process of mineral formation in living organisms. Compared with nonbiogenic minerals, biominerals can be defined as organic–inorganic hybrid materials that have excellent physical and optical properties. In the current study, an artificial protein mimicking the outer shell of crayfish, composed of CaCO3, chitin, and proteins, was developed to facilitate organic–inorganic hybrid material formation by precipitation of calcium carbonate on the chitin matrix. The fusion protein (CaBP-ChBD) was constructed by introducing a short-sequence calcite-binding peptide (CaBP) into the chitin-binding domain (ChBD). Calcium carbonate precipitation experiments by enzymatic urea hydrolysis revealed that a significant increase in the CaCO3 formation was achieved by adding CaBP-ChBD. Also, CaCO3 was efficiently deposited on chitin particles decorated with CaBP-ChBD. Most interestingly, CaBP-ChBD would improve the performance in sand solidification more efficiently and sustainably in the process of biocementation technique. The developed recombinant protein could be used for the sustainable production of organic–inorganic green materials for engineering applications.
Keywords: recombinant protein; hybrid materials; biopolymer; calcium carbonate; biocementation